2018
DOI: 10.35448/jte.v13i1.4182
|View full text |Cite
|
Sign up to set email alerts
|

Determinasi Kepuasan Hedging Dengan Instrumen Derivatif Keuangan

Abstract: This study conducted to see the effect of the company's firm size, leverage, growth opportunity and profitability on the decision of hedging with derivative instruments on manufacturing companies listed on the Indonesian Stock Exchange period 2011-2016. Sample in this study uses 34 companies by using purposive sampling method. This study uses a quantitative approach and data used secondary data. The analytical method used is logistic regression. The results shower that the variable firm size and growth opportu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 1 publication
2
6
0
Order By: Relevance
“…Based on research conducted by Guniarti (2014), Kurniawan and Asandimitra (2018), and Windari and Purnawati (2019), leverage is projected with variable Debt to Equity Ratio (DER) has a significant positive effect on hedging decisions. In comparison, the results of research from Ahmad and Haris (2012), Mediana and Muharam (2016), and Utami et al (2018) showed that DER variables do not affect hedging decisions.…”
Section: Introductionmentioning
confidence: 92%
“…Based on research conducted by Guniarti (2014), Kurniawan and Asandimitra (2018), and Windari and Purnawati (2019), leverage is projected with variable Debt to Equity Ratio (DER) has a significant positive effect on hedging decisions. In comparison, the results of research from Ahmad and Haris (2012), Mediana and Muharam (2016), and Utami et al (2018) showed that DER variables do not affect hedging decisions.…”
Section: Introductionmentioning
confidence: 92%
“…Growth opportunity is an opportunity owned by a company to develop itself in the market (Manova, 2017). According to research conducted by Utami, Sriyanto, and Purbasari (2018), a high company growth opportunity indicates a company's opportunity to enlarge its operations and can make the company maintain its viability. The company needs large funds to finance this growth to take advantage of these opportunities.…”
Section: H1: Liquidity Affects Hedging Decisions the Effect Of Growth...mentioning
confidence: 99%
“…Companies with high growth opportunity indicate that these companies have the profitability to grow and are liked by potential investors. Companies with high growth opportunity tend to carry out more overseas operational activities where companies have to face risks from fluctuations in foreign exchange rates, so companies need to hedge to reduce these risks (Utami, Sriyanto, & Purbasari, 2018). Previous research conducted by Utami, Sriyanto, and Purbasari (2018) stated that growth opportunity proxied by comparing MVE with BVE has a positive influence on hedging decisions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hedging is a contract designed to protect risks against exchange rates. In general, hedging is a risk management measure carried out by investors or shareholders to minimize or avoid possible losses due to exchange rates, interest rates, stock prices or commodities (Utami et al, 2018;OECD, 2013;Nurhandono & Firmansyah, 2017;Lee, 2017) Tax aggressiveness can be affected by financial leases. Setiani (2016) argues that a financial lease is a type of leasing activity where the lessee (customer) has the right to purchase the leased item.…”
Section: Introductionmentioning
confidence: 99%